Independensi Auditor dan Pengaruhnya Terhadap Kualitas Hasil Audit : ( Studi Pada Auditor Inspektorat Kota Gorontalo) - Mahfiza Mahfiza (Al-Buhuts, 2020)
This study aims to determine the effect of auditor independence on the quality of audit results at the inspectorate of Gorontalo city. The method used in this research is descriptive quantitative with a survey approach. The population in this study were 40 auditors at the Inspectorate of Gorontalo City. The results of the research prove that auditor independence has an effect on the quality of the audit results, where in producing the quality of the audit results, it is necessary to increase its independence by maintaining its opinion without being influenced by other parties and having adequate expertise.